Effect of some effective parameters on COD removal from Nam Son landfill leachate by electrocoagulation - Son, Le Thanh; Khai, Le Cao; Linh, Doan Tuan; Anh, Doan Thi (Vietnam Journal of Science and Technology, 2017)
Leachate becomes ahead of wastewaters as being the most difficult to treat due to its complex and widely variable composition. In this research, the leachate treatment performance by electrocoagulation (EC) was studied. The samples of leachate were taken from Nam Son landfill in Hanoi. The effects of factors namely current intensity, electrolysis time, initial pH and anode materials on the EC performance were investigated via chemical oxygen demand (COD) removal efficiencies. The input leachate properties were obtained as COD, NH4+ and pH in the range of around 6247 ± 295, 1270 ± 38 mg/l and 8 ± 0.1, respectively. Mono-polar electrocoagulation unit was carried out in a batch system for leachate treatment with iron electrodes and approximately 1.8 litter of leachate. Firstly, with the increase in current (1 to 4A), the COD removal efficiencies increased from 50.00 to 78.57% (pH = 8 and operating time = 40 min). Secondly, by the increase in operating time, the treatment performance also went up significantly in first 40 min, then nearly level-off at above 73 % (pH=8, current intensity = 3A). In addition, the effect of pH in range of 5 to 10 on the electrocoagulation process was studied and showed the highest treatment efficiencies in neutral and mild alkaline medium, especially between 6 < pH < 8. Finally, the electrode materials made of iron and aluminum was investigated and the result indicated that when the iron anodes were replaced by aluminum, the COD removal efficiency experienced a considerable decline, from 70 to 37.93% (pH = 8 and operating time = 40 min). In combination of all experiments, the optimum operating conditions were achieved as iron electrodes, current intensity of 3A, electrolysis time of 40 min, the raw pH with iron electrodes, resulting the maximum COD removal efficiencies of 73.21%. As a result, the electrocoagulation can be applied to leachate pre-treatment.